Outcomes for Teenage Mothers in the First Years after Birth - Kalb, Guyonne; Leung, Felix; Le, Trinh (My University, 2015)
This study compares the educational, employment, health and partnership outcomes of teenage mothers with outcomes of women first giving birth in their twenties and those without children. The study finds that teenage motherhood has a range of negative effects, some of which worsen over time (e.g. educational outcomes) and others diminish over time (e.g. employment effects). Although some of the associations of teenage motherhood with poorer outcomes in the first years after birth are unlikely to be causal since they disappear after ensuring treatment and control group are comparable, other associations remain strong. Propensity score matching analysis suggests that relative to childless women: teenage mothers are less likely to complete Year 12, be employed, and be in good health; they are more likely to smoke; and have less personal income.
Keywords: Families -- Mothers; Families and relationships; Families; Mothers; Families and relationships